Polyoxovanadate-Based Cyclomatrix Polyphosphazene Microspheres as Efficient Heterogeneous Catalysts for the Selective Oxidation and Desulfurization of Sulfides - Yinghui Hu; Diping Huang; Jing Yan; Zhiliang Miao; Lize Yu; Ningjing Cai; Quanhai Fang; Qiuyu Zhang; Yi Yan (Molecules, 2022)
The [V6O13]2− cluster is successfully immobilized to the polymeric framework of cyclomatrix polyphosphazene via the facile precipitation polymerization between the phenol group symmetrically modified [V6O13]2− and hexachlorocyclotriphosphazene. The structure of the as-prepared polyoxometalate-containing polyphosphazene (HCCP-V) was characterized by FT-IR, XPS, TGA, BET, as well as SEM and zeta potential. The presence of a rigid polyoxometalate cluster not only supports the porous structure of the polymeric framework but also provides an improved catalytic oxidation property. By using H2O2 as an oxidant, the as-prepared HCCP-V exhibited improved catalytic oxidation activity toward MPS, DBT, and CEES, which can achieve as high as 99% conversion. More importantly, the immobilization of POMs in the network of cyclomatrix polyphosphazene also provides better recyclability and stability of the heterogeneous catalyst.